Literary Lapses - Leacock, Stephen, 1869-1944 (Salt Lake City, UT : Project Gutenberg, 2004)
"Literary Lapses" by Stephen Leacock is a collection of humorous essays and stories written in the early 20th century. The book presents a series of witty observations and satirical takes on various aspects of life, education, and social customs, showcasing Leacock's sharp wit and keen insights into human nature. The opening portion of the book introduces readers to a variety of humorous sketches, starting with "My Financial Career," which depicts the protagonist's comical misadventures at a bank as he struggles through the process of opening an account. This is followed by "Lord Oxhead's Secret," a farcical tale of an English lord grappling with the secret of his family while sticking to his aristocratic traditions, particularly in the context of his daughter's potential marriage to an American. Together, these segments set the tone for the collection, illustrating Leacock's adeptness at blending comedy with keen social commentary, making it an engaging read for those who appreciate clever humor. (This is an automatically generated summary.)
My financial career -- Lord Oxhead's secret -- Boarding-house geometry -- The awful fate of Melpomenus Jones -- A Christmas letter -- How to make a million dollars -- How to live to be 200 -- How to avoid getting married -- How to be a doctor -- The new food -- A new pathology -- The poet answered -- The force of statistics -- Men who have shaved me -- Getting the thread of it -- Telling his faults -- Winter pastimes -- Number fifty-six -- Aristocratic education -- The conjurer's revenge -- Hints to travellers -- A manual of education -- Hoodoo McFiggin's Christmas -- The life of John Smith -- On collecting things -- Society chit-chat -- Insurance up to-date -- Borrowing a match -- A lesson in fiction -- Helping the Armenians -- A study in still life: the country hotel -- An experiment with Policeman Hogan -- The passing of the poet -- Self-made men -- A model dialogue -- Bach to the bush -- Reflections on riding -- Saloonio -- Half-hours with the poets: Mr. Wordsworth and the cottage girl; How Tennyson killed the May queen; Old Mr. Longfellow on board the "Hesperus" -- A, B, and C.
Release date is 2004-06-01
Keywords: Humorous stories, Canadian